Visual Strategy of Commercial Photography in the Promotion and Cultural Preservation of Koto Gadang Silver Heritage “Silver Work Leo” - Septia Rahmatul Khairani; Dira Herawati (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Silver craftsmanship of koto gadang is a minangkabau cultural heritage with high aesthetic, historical, andcultural value, developing since the nineteenth century through the distinctive filigree technique. Silverwork leo, established in 1986, plays a role in maintaining the continuity of this silver craft tradition. Afterthe covid-19 pandemic, reputation and sales declined due to decreased tourist visits and insufficient visualpromotion strategies. This condition indicates the need to renew promotional media through a moreprofessional visual approach. This creation-based research aims to produce commercial photography thatvisualizes silver work leo silver products in an informative, aesthetic, and marketable manner. The creationprocess involved outdoor photoshoots using models wearing silver work leo jewelry and baju kuruang torepresent koto gadang cultural identity. Commercial photography functions as a medium to image throughcomposition and lighting, supporting promotion and preservation.